Designing Metallic Microlattices for Energy Absorber Applications1. Issue 3 (14th November 2013) - Schaedler, Tobias A.; Ro, Christopher J.; Sorensen, Adam E.; Eckel, Zak; Yang, Sophia S.; Carter, William B.; Jacobsen, Alan J.; Stephani, Günter; Scheffler, Michael
<x xml:space="preserve">Abstract</x> Emerging capability to fabricate well‐defined, ordered lattice structures offers opportunity to create new energy absorption materials with previously unachieved properties. Metallic microlattices can be designed to maximize energy absorption while not transmitting a stress greater than the injury or damage threshold. The stress–strain response of different microlattice materials is characterized under quasi‐static and dynamic loading and compared to state‐of‐the‐art materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>